Emigracyjne czasopisma literacko-artystyczne i literackie edytowane przez Polaków w Wielkiej Brytanii w XX i XXI wieku = Literary and literary-artistic emigration journals edited by Poles in Great Britain in the 20th and 21st century - Chwastyk-Kowalczyk, Jolanta (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The article presents the segment of literary and literary-artistic emigration journals edited by Poles in Great Britain in the 20th and 21st century, addressed to the intelligentsia. The author has reviewed this niche press market since 1940 to the present day. She discussed the Paris-based "Polish Political and Literary News", which, after the defeat of France, was issued in London as "News", monthly magazines appearing in London: "New Poland", "Before the Dawn", "New Polish Mercury but Very Similar to the Old One and Academic Life", an independent addition to London's "Polish Daily and Soldier?s Daily" entitled "Party of the Youth", from which stemmed "Continents. New Mercury", literary and artistic quarterly "Poets? Press", current half-yearbook "Literary Memoir" and yearbook "Expressions". This article focuses on the last two, because in the 21st century they remained the only representatives of this type of magazines. Historical-retrospective method and press content analysis are used.
Keywords: emigracyjne czasopisma literacko-artystyczne; czasopisma literackie; czasopisma polonijne; Wiadomości Polskie Polityczne i Literackie; rynek prasowy; emigrant literary and artistic magazines; literary magazines; Polish diaspora magazines; press market